Analisis Kehilangan Air pada Daerah Irigasi Lagadar Kabupaten Bandung - Muhammad Nur Azmi; Sulwan Permana (Jurnal Konstruksi, 2026)
Irrigation water plays an important role in supporting the agricultural sector, particularly in Indonesia as an agrarian country. Adequate water availability and proper distribution are key factors in increasing agricultural productivity and ensuring food security. However, water losses due to seepage, leakage, sedimentation, and illegal structures frequently occur in irrigation networks, including the Lagadar Irrigation Area in Bandung Regency, which serves an area of approximately 325 ha. This study aims to analyze the magnitude of water losses and identify the factors causing them. The research adopts a quantitative approach through field studies, involving measurements of inflow and outflow discharge at several channel sections using the float method, as well as analysis of losses due to leakage and seepage using the Moritz equation. Based on discharge measurements conducted over seven consecutive days, the largest water loss was recorded on day 5 at 0.1273 m³/s, while the smallest loss occurred on day 3 at 0.1055 m³/s, with an average water loss of 0.1156 m³/s. These values indicate fluctuations in water losses influenced by the physical condition of the channel and environmental factors. The main factors contributing to water loss are leakage and sedimentation, particularly in the overcrossing sections, which are difficult to maintain, leading to sediment accumulation and a reduction in the effective wetted cross-sectional area. The results of this study are expected to serve as an evaluation reference for irrigation network managers in improving water distribution efficiency and supporting more sustainable water resource management in areas with similar elevation characteristics.